Immune Reconstitution Inflammatory Syndrome in a Case of Nonspecific Orbital Inflammation. Issue 2 (March 2018) - Manta, Alexandra; Ugradar, Shoaib; Murta, Fabiola; Ezra, Daniel; Cormack, Ian
Abstract : The immune reconstitution inflammatory syndrome is an exaggerated abnormal immune response, typically seen in HIV-positive patients following restoration of a normal CD4 count as a result of initiation of antiretroviral therapy. It has been described in relation to either occult opportunistic infections or to a paradoxical relapse of a previously successfully treated infection with negative microbiological cultures. The authors report the case of a 60-year-old HIV-positive African male who presented with 2 episodes of orbital inflammation that occurred in conjunction with improvements of CD4 count following Highly Active Antiretroviral Therapy. This phenomenon was underpinned by biopsies obtained following each episode. Interestingly, on both occasions, he responded well to corticosteroid therapy. Although the soft tissues of the orbits are a common area affected by other inflammatory diseases, it is rare for them to be involved in immune reconstitution inflammatory syndrome. To the authors' knowledge, this is the first case report of immune reconstitution inflammatory syndrome affecting the orbits exclusively. The authors believe that it is probably an underdiagnosed condition and may be erroneously labeled as idiopathic in many cases. This case report inspires us to keep an open mind when dealing with patients on antiretroviral therapy. Abstract : The immune reconstitution inflammatory syndrome is an exaggerated abnormal immune response, typically seen in HIV-positive patients following restoration of a normal CD4 count as a result of initiation of antiretroviral therapy. We report the case of a 60-year-old, HIV-positive African male who presented with 2 episodes of orbital inflammation that occurred in conjunction with improvements of CD4 count following Highly Active Antiretroviral Therapy. To our knowledge, this is the first case report of immune reconstitution inflammatory syndrome affecting the orbits exclusively.